MARKETING STRATEGY IN ENCOURAGING CUSTOMER DECISIONS TO CHOOSE KUR AT BANK NEGARA INDONESIA KCP. SINJAI - Selfiani; Suriati; Irawan, Heri (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2023)
This study aims to find out about. (1) Marketing strategy in encouraging customer's decision to choose credit card at Bank Negara Indonesia Branch Office of Sinjai. (2) Supporting and inhibiting factors of Marketing Strategy in encouraging customers' decisions to choose credit card at Bank Negara Indonesia Branch Office of Sinjai. This research is included in the type of phenomenological research, using a qualitative research approach. The subjects of this research are credit management, marketing, and customers. The data collection methods are interviews, observation, and documentation. While the data analysis technique, data presentation is using data reduction techniques, data presentation, and drawing conclusions. The results of this study indicate that (1) Marketing strategy in encouraging customers' decisions to choose a credit card at Bank Negara Indonesia Sinjai Branch Office has been implemented properly, while the Marketing strategies implemented in encouraging customers' decisions to choose credit are: canvassing or going directly to the field, promotio or marketing through social media, quality of service and word of mouth between customers. The implementation of this strategy has succeeded in encouraging customer decisions to choose foreign exchange credit at Bank Negara Indonesia Sinjai Branch Office. Meanwhile, (2) the supporting and inhibiting factors of marketing strategy in encouraging customers' decision to choose a credit card at Bank Negara Indonesia Indonesia Branch Office of Sinjai can come from the company itself. In marketing People’s BussinesCredit at Bank Negara Indonesia Branch Office of Sinjai; the credit offered has been recognized by the public, partners, and the quality of the company's marketing or field sales, office facilities that support adequate product marketing. The inhibiting factors for marketing strategies in encouraging customers' decisions to choose credit cards are disk communication between customers and the number of competitors.